Post-COVID Pulmonary Fibrosis: Pathophysiological Mechanisms, Diagnostic Tools, and Emerging Therapies - Sabu, Sowparnika Treasa (Journal of Pulmonology and Respiratory Research, 2025)
Post-COVID pulmonary fibrosis has emerged as a significant long-term complication among survivors of severe SARS-CoV-2 infection. This review highlights the underlying pathophysiology, diagnostic modalities, and recent advances in the diagnosis and management of post-COVID pulmonary fibrosis. As global cases of COVID-19 continue to evolve, understanding and addressing this emerging chronic respiratory condition is critical for long-term patient care.